(untitled) (International Journal of Agricultural Research, Innovation and Technology, 2017)
An experiment was conducted to find out the fungal competitors and symptom studies in damaged Oyster Mushroom spawn packets at National Mushroom Development and Extension Center, Savar, Dhaka, Bangladesh. A total of nine fungal competitors of oyster mushroom were isolated and identified namely- Trichoderma harzianum Rifai, T. viride Pers. (Green strain), T. viride Pers. (Yellow strain), T. koningii Oudem, Mucor hiemalis Wehmer, Papulaspora byssina Hotson, Neurospora sp. Shear and B.O. Dodge., Aspergillus flavus Link., and Botryodiplodia theobromae Pat. on the basis of microscopic, morphological and cultural characteristics. To produce oyster mushroom in an eco-friendly manner and to find out their antifungal potency, 23 plant species belonging to 19 families were screened out against isolated nine fungal competitors of oyster mushroom. Among 23 extracts, the maximum (44%) mycelial inhibition of T. harzianum was found due to Aegle marmelos whereas Eclipta alba showed the highest mycelial inhibition (62%) of T. viride (Green strain); in case of T. viride (Yellow strain), Cassia tora exhibited the highest mycelial inhibition (39%); Diospyros cordifolia showed the maximum mycelial inhibition (48%) of T. koningii; Curcuma longa (rhizome) gave the maximum mycelial inhibition (90%) of Neurospora sp. There were no significant effects found to control of P. byssina, B. theobromae, M. hiemalis and A. flavus due to 23 different types of botanicals tested. Trichoderma harzianum, T. viride (Green strain), T. viride (Yellow strain), T. koningii, A. flavus, Neurospora sp. and P. byssina was successfully inhibited by 30, 50 and 70 ppm of fungicide-Bavistin 50 WP but B. theobromae and M. hiemalis were not affected by Bavistin at mentioned concentration. Int. J. Agril. Res. Innov. & Tech. 6 (2): 24-30, December, 2016